2021
DOI: 10.1007/s11356-021-13431-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint forecasting using time series data mining methods: the case of Turkey

Abstract: In the globalizing world, many factors such as rapidly increasing population, production and consumption habits, and economic growth cause climate changes. The carbon footprint is a measure of CO 2 emissions released into the atmosphere, which increases day by day, causing glaciers to melt and increase sea level, reduce water resources, and global warming. For Turkey, as a country trying to complete its economic development, signed international agreements such as the Paris Climate Agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In addition to this research, South Africa was also studied by [187,188], and India, together with Malaysia, Indonesia, Kenya, Mexico, Colombia, and Poland, were investigated by [189]. The European Union was addressed by [190], and concluded that economic factors accelerate environmental degradation; only Turkey was analyzed in isolation from Europe by [191,192]. ASEAN member countries were investigated by [193] and showed that macroeconomic factors contribute to degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this research, South Africa was also studied by [187,188], and India, together with Malaysia, Indonesia, Kenya, Mexico, Colombia, and Poland, were investigated by [189]. The European Union was addressed by [190], and concluded that economic factors accelerate environmental degradation; only Turkey was analyzed in isolation from Europe by [191,192]. ASEAN member countries were investigated by [193] and showed that macroeconomic factors contribute to degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The first input variable of the model is the population, which was also used in the studies carried out by Garip and Oktay (2018), Acheampong et al (2019), Quenard and Roumanie (2021), and Akyol and Uçar (2021) [7,9,13,15].…”
Section: Datasetmentioning
confidence: 99%
“…The second variable is the gross domestic product (GDP), which shows the economic volume of the country. This variable was also used by Radojevic [4,6,8,9,13,15]. Another economic variable used as an input in the model is the industrial production index.…”
Section: Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [34] analyzed the uncertainty of GHG emissions using the parametric Monte Carlo simulation method and the non-parametric bootstrap method, whereas Akyol and Ucar estimated the greenhouse gas emissions of Turkey in the year 2030 using a time series forecasting algorithm in the WEKA (Waikato Environment for Knowledge Analysis) data mining software [35].…”
Section: Introductionmentioning
confidence: 99%